Catheter-related infections: does the spectrum of microbial causes change over time? A nationwide surveillance study. Issue 12 (22nd December 2018) - Buetti, Niccolò; Lo Priore, Elia; Atkinson, Andrew; Widmer, Andreas F; Kronenberg, Andreas; Marschall, Jonas
Abstract : Objectives: To estimate the incidence and epidemiology of catheter-related bloodstream infections (CRBSIs) on a national scale by using prospective epidemiological data from the Swiss Antibiotic Resistance Surveillance System (ANRESIS). Design: Observational study. Setting: National surveillance from 2008 to 2015 of acute hospitals in Switzerland. Participants: We included acute Swiss hospitals that sent blood cultures and catheter tip culture results on a regular basis during the entire study period to the ANRESIS database. Outcome measure: A catheter-related bloodstream infection (termed 'modified CRBSI', mCRBSI) was defined as isolating the same microorganism with identical antibiogram from ≥1 blood cultures (performed ±7 days around the catheter removal) as the one recovered from the catheter tip. Incidence rates of mCRBSI were calculated per 1000 admissions. Results: From 2008 to 2015, the mCRBSI incidence rate decreased from 0.83 to 0.58 episodes/1000 admissions (−6% per year, p<0.001). Coagulase-negative staphylococci, Staphylococcus aureus and fungi all exhibited decreasing trends, while rates of enterococci and Gram-negative bacteria remained stable. Conclusions: The overall incidence of mCRBSI in Switzerland is decreasing; however, the incidence of mCRBSI due to Enterococci and Gram-negative micro-organisms did not change over time. These pathogens may grow in importance in catheter-related infections, which would have clinical implications for the choice of empirical treatment.